1978
DOI: 10.1021/bi00617a004
|View full text |Cite
|
Sign up to set email alerts
|

T4 RNA ligase joins 2'-deoxyribonucleoside 3',5'-bisphosphates to oligodeoxyribonucleotides

Abstract: T4 RNA ligase catalyzes the ATP-dependent addition of a single 2'-deoxyribonucleoside 3',5'-bisphosphate to the 3'-hydroxyl of an oligodeoxyribonucleotide. The bisphosphate is joined to the deoxyoligomer by a 3' leads to 5' phosphodiester bond and the product, which is terminated by a 3'-phosphate, is one nucleotide longer than the substrate. Bisphosphates of dAdo, dCyd, dGuo, dThd, and dUrd are donors and oligodeoxyribonucleotides with dA, dC, dG, dT, or dU 3' termini act as acceptors. The preferred residue f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

1982
1982
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 24 publications
4
37
0
Order By: Relevance
“…The 3Ј cyclic phosphate of DsrA produced during the second ribozyme reaction (15) (20) except that the ATP concentration was 0.1 M (16,21). Labeled RNA was extracted, and unincorporated nucleotides were removed by desalting.…”
Section: Methodsmentioning
confidence: 99%
“…The 3Ј cyclic phosphate of DsrA produced during the second ribozyme reaction (15) (20) except that the ATP concentration was 0.1 M (16,21). Labeled RNA was extracted, and unincorporated nucleotides were removed by desalting.…”
Section: Methodsmentioning
confidence: 99%
“…T4 Rnl1 and T4 Rnl2 are capable of using DNA ligation donors (59-PO 4 ends). T4 Rnl1, but not T4 Rnl2, can use a DNA acceptor (39-OH) (Sugino et al 1977;Hinton et al 1978;McCoy and Gumport 1980), while T4 Rnl2 requires 2 ribonucleotide residues on the acceptor side of the ligation junction . The rates at which ligation is catalyzed for all of the possible combinations of DNA and RNA acceptor donor pairs have not been exhaustively compared, but those that have been measured appear to vary greatly, and for both ligases, the preferred substrates are RNAs (Bullard and Bowater 2006).…”
Section: Poly(a) Tailing Is Sensitive To 29-o-methylation Of the Termmentioning
confidence: 99%
“…If the 3Ј-end of the RNA substrate could be rendered chemically incompetent for circularization and oligomerization, then a blocking oligo may no longer be necessary to achieve 5Ј-adenylation. The use of 3Ј-terminal blocking groups to control T4 RNA ligase-mediated ligation has been reported (Sninsky et al 1976;Uhlenbeck and Cameron 1977;Hinton et al 1978). Indeed, we found that 5Ј-AppRNA formation proceeds on substrate S1 that has a 2Ј,3Ј-cyclic phosphate, in the absence of any DNA blocking oligo (Fig.…”
Section: A 23-cyclic Phosphate On the Rna Substrate Abolishes Both Cmentioning
confidence: 56%
“…Indeed circularization was the first T4 RNA ligase-catalyzed reaction to be studied (Silber et al 1972;. The potential utility of T4 RNA ligase was immediately recognized for intermolecular ligation of mononucleotides or oligonucleotides to other oligonucleotides Walker and Uhlenbeck 1975;Uhlenbeck and Cameron 1977;England and Uhlenbeck 1978a;Hinton et al 1978;Hinton and Gumport 1979;Moseman McCoy and Gumport 1980;Brennan et al 1983;Romaniuk and Uhlenbeck 1983). Often this was in the context of labeling an oligonucleotide substrate with 32 P or a fluorescent probe (Barrio et al 1978;Bruce and Uhlenbeck 1978;England and Uhlenbeck 1978b).…”
Section: Introductionmentioning
confidence: 99%